Hypertension in the military patient. Issue 3 (7th August 2015) - Hunter, Alys; Holdsworth, D A; D'Arcy, J; Bailey, K; Casadei, B
Abstract : Hypertension and hypertension-related diseases are a leading cause of morbidity and mortality worldwide. A diagnosis of hypertension can have serious occupational implications for military personnel. This article examines the diagnosis and management of hypertension in military personnel, in the context of current international standards. We consider the consequences of hypertension in the military environment and potential military-specific issues relating to hypertension.